Preparation and characterization of polystyrene/starch blends for packaging applications - Berruezo, M. (2014)
Polystyrene/thermoplastic starch blends from 90/10 to 50/50 (w/w) were prepared by melt blending. Blends were characterized by scanning electron microscopy (morphology); thermogravimetric analysis (thermal stability and weight content of each component); Fourier transform infrared spectroscopy (identification of functional groups); differential scanning calorimetry (thermal properties); tensile tests (strength, modulus, elongation at break and tenacity) and biodegradation in soil (biodegradability). The biodegradation process was also followed by thermogravimetric analysis calculating the loss of each component after removing the samples from soil at different time intervals. Scanning electron microscopy results showed good starch dispersion in the blend. The Fourier transform infrared spectroscopy analysis suggested that only physical interaction took place between the polystyrene and the thermoplastic starch. The tensile tests revealed a considerable decrease in the mechanical properties of the polystyrene-thermoplastic starch blends as a function of the thermoplastic starch content. The 50/50 blend showed decreases of 48% in the Young´s modulus, 62% in the tensile strength and increases of 62% in the elongation at break, in comparison to neat polystyrene. The biodegradability tests showed that the greater the thermoplastic starch concentration in the blend, the faster the mass loss, which was also confirmed by the thermogravimetric analysis and Fourier transform infrared spectroscopy analysis.